CHARACTERISTICS OF FARM ACCOUNTING POLICY. - V.G’. Abdurahmanov (Scholar Express Journals, 2021)
In this article, the author discusses the accounting policy in farms, its organization and the theoretical basis for this. Also, the essence of the accounting policy is to fill in the organizational and methodological aspects of direct accounting, in the chart of accounts used in them, in the documentation of business transactions, registration, grouping, aggregation and transfer of accounting information to financial reporting forms. He pointed out that it is a bright manifestation in the order of loss and in other respects
Keywords: Farming; accounting; accounting policy; farming